Do the Child Welfare and Protection Services Involve Children in Cases With Parental Mental Health Problems? A Norwegian Case-File Study - Vis, Svein Arild; Lauritzen, Camilla; Christiansen, Øivin; Reedtz, Charlotte (Frontiers in Psychiatry, 2022)
Background: Parental mental health problems is a common source of concern reported to child welfare and protection services (CWPS). In this study we explored to what extent the child was invited to participate in the investigation process. We aimed to study: a) what was the current practice in the child protection service in Norway when the CWPS received a report of concern about children whose parents were affected by mental health problems or substance abuse, b) to what extent were children involved and consulted, c) which factors predicted the decision to involve the children, and d) in cases in which conversations with children were conducted: what was the main content of the conversations. Method: The study was a cross-sectional case file study (N = 1123). Data were collected retrospectively from case records in 16 different child protection agencies. The cases were randomly drawn from all referrals registered in the participating agencies. Differences in how investigations were conducted in cases with and without concerns about parental mental health were analyzed using t-tests and chi-square testes. Predictors of child involvement in cases with parental mental health problems (N=324) were estimated by logistic regression analyses. Results: When the referral to the CWPS contained concerns about parental mental health, there were more consultations with parents, more frequent home visits and the investigation took longer to conclude. The children, however, were less likely to be involved. Children in such cases were consulted in 47.5% of cases. Predictors for involving the children in those cases were child age, concern about the child’s emotional problems and if the child was known from previous referrals. Conclusion: In Norwegian child protection investigations, in which there were concerns about the parent’s mental health, conversations with children were conducted to a significantly lower degree compared to cases where the child’s problem was the main concern. In such cases, the CWPS workers have to overcome a threshold before they consult with the child. The threshold decreases with child age and when case worker already knows the child.